Cooperative Principle Maxims In Whatsapp Conversations Among Undergraduates In The Federal University Of Technology Akure, Ondo State, Nigeria - Adebola, Otemuyiwa Abosede (Advances in Social Sciences Research Journal, 2018)
During interlocution, sentences, clauses, phrases, words are used. The utterances made can then be classified in various ways for the purpose of analysis or research. They can be classified according to length by counting the number of words in each utterance, for instance. The utterances can be classified grammatically or structurally in the English language along a number of dimensions: their clausal type and complexity; active-passive; statement-question-request-exclamatory and so on. This study examines the rate of flouting/obeying of Grice’s Cooperative Maxims in WhatsApp conversations among undergraduates in the Federal University of Technology Akure, Ondo State, Nigeria. Theoretical framework for the study Cooperative Principle by Grice 1975 was used to analyse the data. The data include selected conversations from October 2016 to February 2017. The results revealed that the level of cooperation is high to some extent between the conversationalists in FUTA’s data. The maxims of relation and manner were of the same percentages (7.4) and these revealed that the rate of obscurity and the rate of diversion from the topic of discussion was high. This study therefore recommends that students should be more truthful and concise in making their thoughts known in other to reduce flouting of Maxims of cooperation in conversations.